BIOS-03. REAL WORLD CLINICAL OUTCOMES OF PATIENTS WITH DIFFUSE MIDLINE GLIOMA IN A LONGITUDINAL OUTCOMES REGISTRY. (14th November 2022) - Stuhlmiller, Timothy; Wasserman, Asher; Quinn, Jameson; Shapiro, Mark; Kesari, Santosh
Abstract: We utilized the longitudinal clinical outcomes registry XCELSIOR (NCT03793088) to understand real world outcomes and treatment patterns among patients with diffuse midline glioma. A total of 74 patients were identified with a diagnosis of diffuse midline glioma by pathology or imaging (36 pediatric and 38 adult patients). Median age at diagnosis was 20 years. As of 6/1/2022, 45 patients had expired. Median overall survival (mOS) of the entire cohort was 16.2 months. Cox proportional hazard ratio analysis identified age as the only significant covariate for OS (pediatric HR = 1.59, p=0.04). Pediatric patients had a mOS of 12.9 months and adult patients a mOS of 18.9 months from diagnosis. Frequency of primary tumor location in this dataset was brainstem (35%), thalamus (23%), and pons (20%). Pons location was associated with worst survival (mOS 11.4 months, n=15 patients). The most common anti-cancer interventions among all patients were ONC201 (39 patients), temozolomide (37 patients), bevacizumab (23 patients), panobinostat (8 patients), and immune checkpoint inhibitors (3 patients each, pembrolizumab and nivolumab). In this dataset, no interventions were statistically significant in a Cox proportional hazard model, but both immune checkpoint inhibitors (HR = -1.24, p=0.11) and ONC201 (HR = -0.38, p=0.27) trended toward benefit in the entire population. The subpopulation of patients treated with ONC201 whose tumor also harbored a TP53 mutation displayed a tendency toward activity (n=8); TP53-mutant patients treated with ONC201 had a mOS of 25.0 months vs. TP53 wild-type patients treated with ONC201 had a mOS of 20.3 months. Annotation of data for additional patients is ongoing and updated analyses will be presented at the meeting.